The export-magnification effect of offshoring - Joern Kleinert; Nico Zorell (European Central Bank (ECB), 2012)
In this paper we provide a new explanation for the increase in world trade over the last two decades. We show analytically in a general equilibrium model with heterogeneous firms that a fall in variable offshoring costs boosts trade in differentiated final goods through an intra-industry reallocation of resources towards the more productive firms. That is what we call the export-magnification effect of offshoring. More specifically, lower barriers to offshoring reduce the average costs of inputs for offshoring firms and allow more firms to source cheap foreign intermediates, which improves firm-level price competitiveness. This, in turn, translates into higher export quantities of incumbent exporters (intensive margin) and the entry of new exporters (extensive margin). The increase in final goods trade comes on top of the boost to trade in intermediates. Hence the mechanism proposed in this paper is consistent with the fact that the share of intermediate goods in international trade has remained broadly stable over recent years.
Keywords: F12; F15; F23; 330; international trade; Multinational firms; Offshoring